REVITALIZATION OF NORTH SUMATERA REGION LIBRARY - Anantha, Isfandiary
The design in this thesis is an attempt to increase the role of the North Sumatera Regional Library which continuously degraded. The Library is demanded to improve its role. Restoring its function as the primary source for information, knowledge and social interaction. North Sumatra Regional Library also need to answer the challenges of the future. Its role as a public space that also becomes part of the revitalization. Revitalization is done by the Traditional method of Transfomation the object of maimun palace. Traditional methods chosen so that the building still has the image of a region on the Palace area Maimoon, there are three (3) transformation of the object , “Langkan” as public space, Melayu Ornament “Lebah Bergantung” as building envelope and last “Buah Buton” roof as as roofing with a different form and dimention. Revitalization also creates a public space into the building so that there is an interaction between the interior and the outside. Revitalization will be integrated with the railway station as part of the Creative Facility Programming approach. Programming which combines the functions of a public library, public areas and the train station is in the effort to raise the role of the library. The strategy is to bring the people to get used to visit the library. Maimun Palace shape transformation as a transformation object is done to improve the image of the Palace Maimoon region, making the building as part of the Maimoon Palace. Building mass is formed based on the potential of the area and visual access to the direction of the building - the historic buildings that exist in this region. North Sumatra Regional Library responds axis, public events, building demarcation and height of the building to be a reference for the design of the surrounding buildings in the future.